let A be non empty AltCatStr ; :: thesis: for B, C being non empty reflexive AltCatStr
for G being feasible Covariant FunctorStr over B,C
for M being feasible Contravariant FunctorStr over A,B
for o1, o2 being Object of A
for m being Morphism of o1,o2 st <^o1,o2^> <> {} holds
(G * M) . m = G . (M . m)

let B, C be non empty reflexive AltCatStr ; :: thesis: for G being feasible Covariant FunctorStr over B,C
for M being feasible Contravariant FunctorStr over A,B
for o1, o2 being Object of A
for m being Morphism of o1,o2 st <^o1,o2^> <> {} holds
(G * M) . m = G . (M . m)

let G be feasible Covariant FunctorStr over B,C; :: thesis: for M being feasible Contravariant FunctorStr over A,B
for o1, o2 being Object of A
for m being Morphism of o1,o2 st <^o1,o2^> <> {} holds
(G * M) . m = G . (M . m)

let M be feasible Contravariant FunctorStr over A,B; :: thesis: for o1, o2 being Object of A
for m being Morphism of o1,o2 st <^o1,o2^> <> {} holds
(G * M) . m = G . (M . m)

let o1, o2 be Object of A; :: thesis: for m being Morphism of o1,o2 st <^o1,o2^> <> {} holds
(G * M) . m = G . (M . m)

let m be Morphism of o1,o2; :: thesis: ( <^o1,o2^> <> {} implies (G * M) . m = G . (M . m) )
set I = the carrier of A;
reconsider s = the MorphMap of M . (o1,o2) as Function ;
reconsider r = (( the MorphMap of G * the ObjectMap of M) ** the MorphMap of M) . (o1,o2) as Function ;
reconsider t = ( the MorphMap of G * the ObjectMap of M) . (o1,o2) as Function ;
A1: dom (( the MorphMap of G * the ObjectMap of M) ** the MorphMap of M) = (dom ( the MorphMap of G * the ObjectMap of M)) /\ (dom the MorphMap of M) by PBOOLE:def 19
.= [: the carrier of A, the carrier of A:] /\ (dom the MorphMap of M) by PARTFUN1:def 2
.= [: the carrier of A, the carrier of A:] /\ [: the carrier of A, the carrier of A:] by PARTFUN1:def 2
.= [: the carrier of A, the carrier of A:] ;
A2: dom the ObjectMap of M = [: the carrier of A, the carrier of A:] by FUNCT_2:def 1;
A3: [o1,o2] in [: the carrier of A, the carrier of A:] by ZFMISC_1:def 2;
assume A4: <^o1,o2^> <> {} ; :: thesis: (G * M) . m = G . (M . m)
then A5: <^(M . o2),(M . o1)^> <> {} by FUNCTOR0:def 19;
then A6: dom (Morph-Map (M,o1,o2)) = <^o1,o2^> by FUNCT_2:def 1;
A7: <^(G . (M . o2)),(G . (M . o1))^> <> {} by ;
( (G * M) . o1 = G . (M . o1) & (G * M) . o2 = G . (M . o2) ) by FUNCTOR0:33;
hence (G * M) . m = (Morph-Map ((G * M),o1,o2)) . m by
.= r . m by FUNCTOR0:def 36
.= (t * s) . m by
.= t . ((Morph-Map (M,o1,o2)) . m) by
.= t . (M . m) by
.= ( the MorphMap of G . ( the ObjectMap of M . (o1,o2))) . (M . m) by
.= (Morph-Map (G,(M . o2),(M . o1))) . (M . m) by FUNCTOR0:23
.= G . (M . m) by ;
:: thesis: verum